Theorizing Pada Teori Pengelolaan Modal Kerja: Relasi Aset Lancar Dan Kewajiban Lancar - Shalahuddin Haikal (Jurnal Ekonomi dan Bisnis, 2016)
Current assets and current liabilities relation is one of the traditional topics of financial management. Through algebra operations, both relations acquired current ratio and net working capital which became a postulate, called the rule of thumbs: current ratio must be greater than 1, and net working capital has to be positive. Based on the findings in two IDX’s listed companies, this paper questioning the validity of those rule of thumbs, based on Operation Management, Financial Market evolution and Corporate Governance. This is not an empirical research, this is a theorizing effort which forgotten by scholars in the field of business and management.